ISSEP 2018 The 11th International Conference on Informatics in Schools - Поздняков, Сергей Николаевич (Computer Tools in Education, 2017)
The International Conference on Informatics in Schools: Situation, Evolution and Perspectives (ISSEP) is a forum for researchers and practitioners in the area of Informatics education, in both primary and secondary schools. The conference provides an opportunity for educators and researchers to reflect upon the goals and objectives of this subject matter, its curricula, various teaching and learning paradigms and topics, as well as the connections to everyday life -- including the various ways of developing Informatics Education in schools.